2019
DOI: 10.1139/cjps-2018-0251
|View full text |Cite
|
Sign up to set email alerts
|

Herbage biomass and its relationship to soil carbon under long-term grazing in northern temperate grasslands

Abstract: While northern temperate grasslands are important for supporting beef production, it remains unclear how grassland above- and belowground biomass responds to long-term cattle grazing. Here, we use a comprehensive dataset from 73 grasslands distributed across a broad agro-climatic gradient to quantify grassland shoot, litter, and shallow (top 30 cm) root biomass in areas with and without grazing. Additionally, we relate biomass to soil carbon (C) concentrations. Forb biomass was greater (p < 0.05) in grazed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 34 publications
0
9
1
Order By: Relevance
“…Moreover, it highlights the need for more in-depth studies into the specific role of plant compositional changes under grazing for their ability to regulate ecosystem stability. Findings from two studies conducted at the same sites as ours showed that species richness increased with ongoing grazing (Lyseng et al, 2018;Bork et al, 2019), but we found no evidence of association between species richness and ANPP sensitivity to precipitation. The result is unexpected given the fact that species richness is considered an important determinant of changes in ecosystem productivity and stability (Isbell et al, 2009;Hallett et al, 2014;Tilman et al, 2014).…”
Section: Discussioncontrasting
confidence: 75%
See 3 more Smart Citations
“…Moreover, it highlights the need for more in-depth studies into the specific role of plant compositional changes under grazing for their ability to regulate ecosystem stability. Findings from two studies conducted at the same sites as ours showed that species richness increased with ongoing grazing (Lyseng et al, 2018;Bork et al, 2019), but we found no evidence of association between species richness and ANPP sensitivity to precipitation. The result is unexpected given the fact that species richness is considered an important determinant of changes in ecosystem productivity and stability (Isbell et al, 2009;Hallett et al, 2014;Tilman et al, 2014).…”
Section: Discussioncontrasting
confidence: 75%
“…We found that an increased contribution of forb biomass to total ANPP at the expense of grasses led to an increased ANPP sensitivity to precipitation, and this occurred specifically in grazed rather than non‐grazed grasslands (Figure 3). Previous long‐term grazing studies report that grazing has a deterministic impact on plant functional group composition (Verón & Paruelo, 2010; Gaitán et al, 2014; Irisarri et al, 2016) and their contribution to total ANPP (Bork et al, 2012; Bork et al, 2019), which includes a decline in grasses under grazing. Together these results strongly suggest that any compositional shifts induced by grazing, even among coarse plant functional groups, are likely to account for differences in ANPP sensitivity among ecosystems with comparable mean annual precipitation (Verón & Paruelo, 2010; Irisarri et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, we observed the following patterns of response to drought in this experiment: immediate changes in soil moisture content, followed by shifts in species composition (though not richness or evenness), but inconsistent effects on ANPP. This may chiefly be through variation in the abundance of graminoids, which contribute most to the stability of productivity to precipitation in the region (Batbaatar et al, 2021;Bork et al, 2019). The positive link between the effects of reduced precipitation on species composition and evenness further suggests that changes in the abundance of graminoids may have led to differences in species composition between the ambient and reduced precipitation treatments.…”
Section: Discussionmentioning
confidence: 99%